[1993] Proceedings IEEE Micro Electro Mechanical Systems
DOI: 10.1109/memsys.1993.296916
|View full text |Cite
|
Sign up to set email alerts
|

High-power and high-efficiency electrostatic actuator

Abstract: The authors have previously developed two types of concatenated electrostatic actuators which are driven by pulse excitation profiles. One of these actuators had excellent performance comparable to that of electromagnetic motors. However, the efficiency of the driving circuit for the actuator was insufficient for practical applications. To improve the efficiency, a new type of electrostatic acluator that can be driven by an ac excitation profile was developed. The new actuator is a linear surface-drive actuato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Both films are made using flexible printed circuit (FPC) technology. In both of them, three-phase parallel electrodes, which are aligned with regular intervals like 200 µm, are fabricated [18,19].…”
Section: Structure and Principle Of The Electrostatic Motormentioning
confidence: 99%
“…Both films are made using flexible printed circuit (FPC) technology. In both of them, three-phase parallel electrodes, which are aligned with regular intervals like 200 µm, are fabricated [18,19].…”
Section: Structure and Principle Of The Electrostatic Motormentioning
confidence: 99%
“…Such an idea was demonstrated by Niino et al in the surface drive type electrostatic film motor named DEMED (dual excitation multi-phase electrostatic drive) [10]. A maximum power-to-weight ratio of 230 W/kg [11] and a thrust force of 310 N [12] was demonstrated with this motor, which shows enough performance to replace electromagnetic motors in macro-scale applications.…”
Section: Introductionmentioning
confidence: 96%
“…On the other hand, in some industrial or scientific equipments, such as electron beam (EB) lithography system and magnetic resonance imaging (MRI) scanners, nonmagnetic actuators are required that do not interfere with their functions [1] [2]. To fulfill those requirements, various new actuators such as pneumatic actuators, ultrasonic actuators, shape-memory-alloy actuators (SMA), and electrostatic actuators have been studied [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic motors were originally well-known in the field of micro-machines because of its high power density in micro region. However, recent studies have revealed that even centimeter-sized electrostatic actuators can possess high power density by patterning fine electrodes on a large plastic film using the flexible printed circuit (FPC) technology [7][8][9], which are called electrostatic film motors. For example, the film motor called dual excitation multiphase electrostatic drive (DEMED) showed superior output performance (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation